Ichthyoplankton and plastic waste drift in a river in the Amazon Basin, Brazil - Oliveira, Lucas S.; Oliveira-Junior, José M. B.; Cajado, Ruineris A.; Silva, Fabíola K. S.; Zacardi, Diego M. (Frontiers in Environmental Science, 2023)
Egg and larvae drift is a key mechanism for early fish stages to colonize nursery and growth areas and provides insights into ichthyofauna spawning times and spawning locations – crucial information for understanding fish biology. In the Tapajós River, Amazon Basin, no study has investigated the drift of ichthyoplankton along the hydrological phases nor the occurrence and dispersion of plastic waste associated with plankton. Thus, we aimed to present an overview of the spatio-temporal drift of ichthyoplankton and plastic waste in this river. Fish larvae belonging to 10 taxonomic orders and with an average size of 4.98 mm ± 3.14 mm were captured. Clupeiformes larvae occurred in all hydrological phases and reproductive peaks for other orders were recorded. Plastic waste was classified into 20 types according to color and shape and average size of 1.55 mm ± 1.27 mm. Green fragments and blue filaments were the most abundant. We found the highest density of fish eggs and larvae drifting during the drought phase in stretches with greater environmental structure, whereas plastics were more abundant during the receding water phase in more turbulent stretches that have impacts from illegal mining. No correlation was recorded between the density of ichthyoplankton with plastics, however, drifting of these two was observed in all hydrological phases and sampled sectors. This is worrying because, although we did not analyze the ingestion of plastics by fish larvae, plastic waste can enter the nursery areas of the Tapajós River and reduce the function of these areas for fish. Here we discover through the high densities of fish eggs and larvae deriving that the Tapajós River is an important reproduction site for ichthyofauna, and that the presence of different landscape configurations prove to be a key factor in the dispersion, retention and development of ichthyoplankton and plastic waste.